Challenges and Strategies of Informatics Teachers in Integrating Interactive Technology in Classrooms - Rompas, Parabelem T. D.; Nelwan, Stevani Alen; Iroth, Rendy Maxsi; Simboh, Juneitly Margret; Batmetan, Johan Reimon (International Journal of Information Technology and Education, 2025)
This study aims to identify the challenges faced by informatics teachers in integrating interactive technology into classroom learning and the strategies used to overcome these obstacles. A descriptive qualitative approach was employed with data collected through in-depth interviews, classroom observations, and document analysis. The findings reveal four major categories of challenges: limited digital infrastructure, teachers’ technological competence, varied student readiness, and limited instructional time. Informatics teachers addressed these challenges through self-training, the use of lightweight and free applications, strengthening teacher collaboration, developing interactive learning materials, and implementing more structured digital classroom management. The study recommends enhanced institutional support through the provision of appropriate devices, continuous training, and reinforcement of digital learning policies to achieve optimal integration of interactive technology.